209k views
5 votes
Ahh heyy ! I really need help with these :)

Ahh heyy ! I really need help with these :)-example-1
User SatAj
by
5.1k points

1 Answer

2 votes

To solve this problem we just have to add the opposite number to the number inside the parenthesis (next to the blank space) on both sides of the equation, the x will represent the blank space

a)


\begin{gathered} x+(-25)=34 \\ x+(-25)+25=34+25 \\ x+0=59 \\ x=59 \end{gathered}

The unknown number is 59.

b)


\begin{gathered} x+26=12 \\ x+26-26=12-26 \\ x=-14 \end{gathered}

The unknown number is -14.

c)


\begin{gathered} 8+x=-24 \\ 8-8+x=-24-8 \\ x=-32 \end{gathered}

The unknown number is -32.

d)


\begin{gathered} -12+x=-24 \\ -12+12+x=-24+12 \\ x=-12 \end{gathered}

The unknown number is -12.

e)


\begin{gathered} -15+x=-28 \\ -15+15+x=-28+15 \\ x=-13 \end{gathered}

The unknown number is -13.

f)


\begin{gathered} x+18=-3 \\ x+18-18=-3-18 \\ x=-21 \end{gathered}

The unknown number is -21.

User Noro
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.